EFEKTIFITAS ABDOMINAL LIFTING TERHADAP NYERI PADA IBU BERSALIN KALA I DI KLINIK PRATAMA JAMBU MAWAR - Rini Hariani Ratih; Yusmaharani Yusmaharani (LPPM Universitas Abdurrab, 2024)
Pain during labor is a manifestation of contractions (shortening) of the uterine muscles. This contraction causes pain in the waist, stomach area and spreads towards the thighs. The level of labor pain is described by the intensity of pain perceived by the mother during the birth process, if not handled properly, it can increase anxiety or worry to the point of depression and has the effect of increasing the hormone adrenaline, affecting the mother's cardiac output and decreasing uteroplacental perfusion and can cause prolonged labor. One step in reducing pain is by applying abdominal lifting. The research method uses a quasi experimental approach. This study aims to determine the effectiveness of abdominal lifting in reducing labor pain. The population in this study was all mothers in the first stage of labor at the Pratama Guava Rose Clinic. The sample collection method was purposive sampling with a sample size of 15 people. Data were collected using a pain intensity scale during the pretest before the intervention and posttest after the intervention. The results of the univariate research showed that the average labor pain before the abdominal lifting technique was 6.80 with a standard deviation of 1.85, while the results after the abdominal lifting technique were 3.93 with a standard deviation of 1.09. The results of the bivariate research showed that the abdominal lifting technique was effective in reducing pain in the first stage of labor with a p value of 0.002. It is hoped that respondents and health workers can apply the abdominal lifting technique during labor to help reduce the pain felt during labor so as to increase maternal comfort.